(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article is based on the development of methodical, professional and creative abilities of future chemistry teachers in the 4+2 practical process, teaching them the methodology of conducting experimental experiments, and the methodological foundations of the science of pedagogy and the need for pedagogical skills. will go.